Customer preference for apparel product based on its attribute: a conjoint analysis approach - Putri, Navissa Syahnindita; Belgiawan, Prawira Fajarindra (Journal of Innovation, Business and Entrepreneurship, 2019)
In 2015, the apparel industry contributed 18.15% of the country’s creative economy. And by 2018, clothing and beauty are the categories of goods and services that are most in-demand by Indonesian people. However, not knowing what does the customer prefer in an apparel product can result in long experiments processes and unintended product fit. Therefore, this research is conducted to explore customer preference of apparel by assessing its product attributes. A total of 408 respondents has participated in the research. The researcher used non-probability sampling and used a questionnaire to collect the data. Conjoint Analysis is used to analyze the respondents’ preferences for products that are described by attributes and levels in the form of combination cards; thus, it can be an input for fashion companies. The result of the research reveals that the preferences of apparel product according to the customer by its attributes are oversized fit apparel in neutral colors that displays a feminine or masculine style or silhouette. Another result revealed that the most important product attribute according to the customers’ preference is the color. The researcher recommends to conduct future research further to explore more of the product attributes that might influence the customer preference. Keywords: apparel, conjoint analysis, customer preference, fashion, product attributes